Helping hands - Panayides, Angelos (My University, 2024)
This year’s festival highlights AI’s role in driving progress, enhancing creativity, and fostering global connections. Participants are invited to address critical contemporary issues and promote social change through innovative design. The theme encourages designers to explore the transformative impact of AI on our world, encompassing topics such as sustainability, global perspectives, innovation, societal transformation, cultural integration, and the synergy between creativity and technology. Designers are encouraged to select aspects that resonate with their interests andexpertise and express their creative vision on how AI is shaping the future. EIPF serves as a source of inspiration and education for students and professionals in graphic art, design, and related fields.Participants can learn from leading practitioners, engage in critical discourse, and showcase their interpretations of AI’s impact on creativity. EIPF stands as a prominent platform for poster design in the MENA region, with a dedicated focus on promoting creativity, facilitating intercultural exchange, shedding light on critical contemporary issues, and driving social change through innovative design.
Keywords: Emirates International Poster Festival (EIPF)